The Science of Why We Exist: A History of the Universe from the Big Bang to Consciousness - Coulson, Tim (New York, NY : Pegasus Books, Ltd, 2024)
From the Big Bang and the evolution of the genetic code to the birth of consciousness, this is the extraordinary story of the chain of events that led to human life on earth. Have you ever wondered why you exist? What had to happen for you to be alive and conscious? Scientists have come a long way in answering this question, and this book describes what they have found out. It also examines whether our existence was inevitable at the universe's birth 13.77 billion years ago--or whether we are just incredibly lucky. The book is aimed at readers who are interested in science but are not experts. Written in an entertaining and accessible style, the narrative begins by describing how scientists discover facts before taking the reader on a journey from the Big Bang to the creation of the human genome. Covering physics, astronomy, chemistry, earth sciences, the emergence of life, evolution, consciousness, the rise of humanity, and how our personalities are moulded by genes, chance, and the environment, the journey explains how the universe started as point of intense energy that over time, in our corner of the universe, resulted in our wonderful planet--and in you.
Keywords: Cosmology | Evolution| Personality | Physics. |Astronomy | Chemistry. | Evolution. Consciousness. | Human genome.|Big bang theory |Cosmologie.